Study on Computed Tomography (CT) Guided Transthoracic Fine Needle Aspiration Cytology (FNAC) in the Diagnosis of Intrathoracic Mass Lesions - Not Approachable by USG - Sultana, Mosammat Arina; Quddus, Abdul; Alam, Mohammad Taharul; Islam, SK Md Jaynul (Bangladesh Armed Forces Medical Journal, 2024)
Background: Intrathoracic mass is a general issue encountered by the physicians in whole world including Bangladesh. Accurate diagnosis is important for proper management. Percutaneous fine needle aspiration cytology (FNAC) has been extensively utilized and widely accepted as an important means of diagnostic technique. This study was performed to know and justify the computed tomography (CT) guided FNAC as a diagnostic modality for the diagnosis of intrathoracic masses which are non-approachable by ultrasonography (USG). Methods: It was a descriptive type of cross sectional study and conducted among 30 patients having ultrasonologically non approachable intrathoracic masses during the period of Feb 2016 to July 2016 in Combined Military Hospital (CMH), Dhaka considering selection criteria and informed written consent using purposive sampling technique. FNAC was done in all the patients. After further investigation, a definitive diagnosis was made. The analysis of the surgical specimen, the biopsy, the therapeutic response, and the clinical follow-up all contributed to the ultimate diagnosis. A comparison was done between the cytological and final diagnosis for thirty cases. Ethical issues were properly addressed. Results: Initially CT guided FNAC was carried out on all patients. Conclusive cytological diagnosis was possible in 28 patients yielding 93.33% diagnostic accuracy. FNAC diagnosed 24 cases as malignant intrathoracic mass, 04 as benign lesion and 02 undiagnosed due to inadequate tissue material. In final diagnosis 25(75%) diagnosed as malignant and 05(25%) diagnosed as benign. Diagnosis of two patients was impossible by FNAC due to inadequate tissue material. Conclusion: CT guided FNAC of intrathoracic mass allow early diagnosis with lesser trauma and lower cost. This procedure avoided more invasive diagnostic surgery. Bangladesh Armed Forces Med J Vol 56 No (2) December 2023, pp 10-16